Sistem Bantu Pemilihan Rumah Kos dengan Weighted Product dan Geographic Information System - Rini Indriati; Patmi Kasih (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2017)
Internet with dynamic web is used as a means of information and promotion has been used by many people in various fields. Auxiliary facility information system with search and recommendation is needed for people who are ignorant about the information required. The height of new students, mostly from outside Kediri looking rooming house around the campus of the University of Nusantara PGRI Kediri, attracted the attention of researchers to design a dynamic web searches boarding houses are equipped with the implementation method of Weighted Product (WP) for auxiliary systems search rooming house in accordance with the criteria boarding house search. The system is equipped with a Geographic Information System (GIS) to determine the position of the boarding house recommended. The system is made with the theme of decision support. Algorithm Implementation WP done based on criteria rental price of rooms, amenities, and distance from campus boarding houses UN PGRI Kediri. Sample data is 10 boarding houses were selected randomly around campus with distances and different facilities. With the implementation of Weighted Product, the system is able to provide ratings information rooming house based on the calculation of each criterion, the ranking is based on price, location or distance to search boardinghouse can select desired a rooming house. Based on the test results and analysis system, concluded that the system can help facilitate the search for a boarding house close to campus UN PGRI Kediri pretty well.